2022
DOI: 10.1073/pnas.2206986119
|View full text |Cite
|
Sign up to set email alerts
|

A single helix repression domain is functional across diverse eukaryotes

Abstract: The corepressor TOPLESS (TPL) and its paralogs coordinately regulate a large number of genes critical to plant development and immunity. As in many members of the larger pan-eukaryotic Tup1/TLE/Groucho corepressor family, TPL contains a Lis1 Homology domain (LisH), whose function is not well understood. We have previously found that the LisH in TPL—and specifically the N-terminal 18 amino acid alpha-helical region (TPL-H1)—can act as an autonomous repression domain. We hypothesized that homologous domains acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…In contrast, mLisH failed to rescue repression, indicating that the conserved residues in the H1 domain that direct LisH dimerization are required for the activity of ScTAF5 in its role in repression. This finding is consistent with cross-kingdom analyses of other LisH domains 22 . We engineered an Auxin inducible degron (AID) version of ScTaf5 (AID-Taf5, Figure 5I) where the degron was fused to the N-terminus of ScTaf5 and observed that this approach did not reduce function of the Taf5 protein (Figure 5I).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, mLisH failed to rescue repression, indicating that the conserved residues in the H1 domain that direct LisH dimerization are required for the activity of ScTAF5 in its role in repression. This finding is consistent with cross-kingdom analyses of other LisH domains 22 . We engineered an Auxin inducible degron (AID) version of ScTaf5 (AID-Taf5, Figure 5I) where the degron was fused to the N-terminus of ScTaf5 and observed that this approach did not reduce function of the Taf5 protein (Figure 5I).…”
Section: Resultssupporting
confidence: 90%
“…We observed a significant reduction in CD4 abundance when TPLN188 was recruited to the CD4 promoter region, compared to a control guide (Figure 5K). Interestingly, the HsTBL1 N-terminal domain (N98), which we previously found to be able to replace TPL in our synthetic yeast assay 22 , was equally efficient at repressing CD4 as ZIM3 (Figure 5K).…”
Section: Tpl Requires Components Of the Nucleation Step Of The Transc...mentioning
confidence: 68%
See 3 more Smart Citations